Epictetus on Death - Esra ÇAĞRI MUTLU (Gaziantep Üniversitesi Sosyal Bilimler Dergisi, 2018)
The philosopher in Epictetus’ Discoursesis Socrates. Moreover, someone who reads Stoic philosophy over Epictetus, can think that the school Epictetus belonged is a Socratic school. The basic reason for this that there are some similarities between Socrates’ and Stoics’ ideas on death and the relation of death with philosophy. Stoic philosophers especially take Socratic life as an example for Stoic life style. Socrates’ ideas on self-control, his negligence on physical and emotional things affect them. Yet, there are some differences between their ideas. Socrates takes death as soul’s escape from body and becoming free. Soul returns to its home and becomes immortal again by death and what gives this chance to it is philosophy and, in this manner, philosophy is a practice of death. When we return to Stoic philosophy firstly, we could see that they don’t accept soul as an immortal entity like Socrates or Plato. On the contrary they believe that the soul modifies itself. So, for Epictetus, unlike Plato’s two-parted soul: rational and irrational, soul doesn’t have two parts. Therefore, within this context we could see that Stoic philosophers accept death not as the escape of the soul nor something which we should be afraid of. According to them, death is a natural thing and so there is no point to be afraid of it. In this manner, I’ll try to analyze the relation of death and philosophy in Stoic philosophy, especially in Epictetus in this paper.